Are U.S. Cities Underpoliced? Theory and Evidence - Chalfin, Aaron; McCrary, Justin (The Review of Economics and Statistics, 2018)
We document the extent of measurement errors in the basic data set on police used in the literature on the effect of police on crime. Analyzing medium to large U.S. cities over 1960 to 2010, we obtain measurement error-corrected estimates of the police elasticity. The magnitudes of our estimates are similar to those obtained in the quasi-experimental literature, but our approach yields much greater parameter certainty for the most costly crimes, the key parameters for welfare analysis. Our analysis suggests that U.S. cities are substantially underpoliced.